The origin of the bird's beak: new insights from dinosaur incubation periods. (23rd May 2018) - Yang, Tzu-Ruei; Sander, P. Martin
Abstract : The toothless beak of modern birds was considered as an adaption for feeding ecology; however, several recent studies suggested that developmental factors are also responsible for the toothless beak. Neontological and palaeontological studies have progressively uncovered how birds evolved toothless beaks and suggested that the multiple occurrences of complete edentulism in non-avian dinosaurs were the result of selection for specialized diets. Although developmental biology and ecological factors are not mutually exclusive, the conventional hypothesis that ecological factors account for the toothless beak appears insufficient. A recent study on dinosaur incubation period using embryonic teeth posited that tooth formation rate limits developmental speed, constraining toothed dinosaur incubation to slow reptilian rates. We suggest that selection for tooth loss was a side effect of selection for fast embryo growth and thus shorter incubation. This observation would also explain the multiple occurrences of tooth loss and beaks in non-avian dinosaur taxa crownward of Tyrannosaurus . Whereas our hypothesis is an observation without any experimental supports, more studies of gene regulation of tooth formation in embryos would allow testing for the trade-off between incubation period and tooth development.